Enhancing light sources color homogeneity in high-power phosphor-based white LED using ZnO particles - Anh-Minh D. Tran; Nguyen Doan Quoc Anh; Nguyen Thi Phuong Loan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
Color uniformity is one of the essentials for the on-going development of WLED. To achieve a high color uniformity index, increasing the scattering events within the phosphor layers was reported to be the most efficient method and in this article, ZnO is the chosen material to apply in this method. After analyzing the scattering properties through the scattering cross-section , scattering coefficient  and scattering phase function , the which outcomes comfirm that ZnO can enhance the scattered light in the phosphor layers. Moreover, the findings from the study of ZnO concentration from 2% to 26% suggest that color uniformity also depends on the fluctuation of ZnO concentration, therefore, to control color uniformity the focus should be implied on both size and concentration of ZnO. The experimental results from this research show that the luminous flux of WLED is at the peak if the concentration of ZnO is at 6%, and when the concentration of ZnO is at 18% and has 100 nm particles size, the ΔCCT reaches the lowest level. The final choice should be based on the desired characteristic of WLEDs, however, if the WLED need to excel in both luminous flux and ΔCCT then 6% ZnO concentration with particles size from 100 nm-300 nm is the optimal choice.